2020
DOI: 10.2147/clep.s243531
|View full text |Cite
|
Sign up to set email alerts
|

<p>Sociodemographic Characteristics Associated with Contacts to Emergency Medical Services and Out-of-Hours Primary Care: An Observational Study of 2.3 Million Citizens</p>

Abstract: Background: Out-of-hours (OOH) health care services are often divided into emergency medical services (EMS) and OOH primary care (OOH-PC). EMS and many OOH-PC use telephone triage, yet the patient still makes the initial choice of contacting a service and which service. Sociodemographic characteristics are associated with help-seeking. Yet, differences in characteristics for EMS and OOH-PC patients have not been investigated in any large-scale cohort studies. Such knowledge may contribute to organizing OOH ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…A previous Danish study, also with data from 2016, found an association between education and likelihood of contacting EMS where low education was associated with greater likelihood of calling 1-1-2. 8 In addition, a Canadian study have shown that patients who are frequent users of ambulances have difficulty getting the money to last a month. 19 Another Danish study based on data from a medical helpline in the capital, Copenhagen, covering 1.8 million people, found that callers with low income were less often triaged to subsequent face-to-face clinical assessment compared with callers with middle/high SES and the same trend was observed for 30-day mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous Danish study, also with data from 2016, found an association between education and likelihood of contacting EMS where low education was associated with greater likelihood of calling 1-1-2. 8 In addition, a Canadian study have shown that patients who are frequent users of ambulances have difficulty getting the money to last a month. 19 Another Danish study based on data from a medical helpline in the capital, Copenhagen, covering 1.8 million people, found that callers with low income were less often triaged to subsequent face-to-face clinical assessment compared with callers with middle/high SES and the same trend was observed for 30-day mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Co-variates are factors related to frequent use of emergency health services for people living in high-income countries, 8 , 19 which are also potentially related to socioeconomic position and therefore potential confounding factors. Included covariates were sex, age, cohabitation and comorbidity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…patients presenting with chest pain [ 14 ]. The association of EMS utilization with age [ 15 17 ] as well as frailty [ 18 ] has likewise been described. Male gender did not constitute an independent EMS utilization predictor in our cohort, as opposed to other studies [ 16 , 19 ] not limited to respiratory patients.…”
Section: Main Textmentioning
confidence: 99%
“…family members for transport, but this remains speculative. In this context, a large observational study from Denmark had identified living alone as a determinant of utilizing EMS, besides age, low income and receipt of cash benefits [ 17 ].…”
Section: Main Textmentioning
confidence: 99%